Lamentations, Robin B. Salters : book review - Kotzé, Gideon R. (Old Testament essays, 2011)
This new commentary on Lamentations forms part of the newly commissioned International Critical Commentary (ICC) series. The stated goal of this commentary series is "to bring together all the relevant aids to exegesis, linguistic and textual no less than archaeological, historical, literary, and theological, to help the reader to understand the meaning of the books of the Old and New Testaments." In this first-rate commentary on Lamentations, Robin Salters has done a sterling job of reaching this goal.